Azadirachtin in combination with emamectin benzoate and abamectin increases efficacy against brinjal shoot and fruit borer, Leucinodes orbonalis Guenee - Md. Mahi Imam Mollah (Journal of Entomological and Acarological Research)
Brinjal shoot and fruit borer (BSFB) is a serious insect pest of brinjal, causing significant damage and yield loss in Bangladesh. Chemical insecticides having toxic effects are frequently applied to control this pest. The present study was conducted with two insecticides, emamectin benzoate and abamectin individually or in combination with plant-origin azadirachtin to combat BSFB. The insecticides were applied at 7-day intervals using a knapsack sprayer. Though all the insecticides control BSFB, emamectin benzoate 1% + azadirachtin and abamectin 1.8% + azadirachtin were found to be most effective, providing 89.34% and 81.55% shoot infestation reduction, 93.34% and 85.11% fruit infestation reduction (number basis), and 94.91% and 85.27% fruit infestation reduction (weight basis), respectively. The highest marketable yield was obtained from abamectin 1.2% + azadirachtin (2.32-ton ha-1 harvest-1). The same treatment confirmed the highest gross yield (2.72-ton ha-1 harvest-1). However, the highest individual weight of marketable fruit was obtained from abamectin 1.2% + azadirachtin (47.30 g). Therefore, emamectin benzoate 1% + azadirachtin and abamectin 1.8% + azadirachtin can be recommended for BSFB control, while abamectin 1.2% + azadirachtin is recommended for increasing fruit yield. However, further investigation is required.